DETERMINANTS OF SUBJECTIVE WELL-BEING: EVIDENCE OF URBAN INDONESIA - Nandini, Dewi; Afiatno, Bambang Eko (Jurnal Ekonomi Pembangunan, 2020)
Happiness studies on economics have increasingly arisen since the uprising of the Easterlin Paradox phenomenon. Besides its populous side, the urban area has more complicated problems than rural. This research aims to analyze the determinants of happiness in urban Indonesia. We use the latest data from the Happiness Measurement Survey 2017 conducted by the BPS-Statistic Agency of Indonesia. Taking 30,665 observations, we apply the Ordered Logit Estimation technique (including G2-likelihood ratio test, Wald statistical test, and Hosmer-Lemeshow goodness of fit test) to analyze the determinants of happiness. We found that Easterlin Paradox does not exist in urban area Income, education, health, marrying, internal-external relationship, a satisfying job, positive feeling, and a meaningful life have a positive impact on happiness. Generally, these findings support some previous studies' findings.